Hokkaidō 150: settler colonialism and Indigeneity in modern Japan and beyond. Issue 4 (2nd October 2019) - Grunow, Tristan R.; Nakamura, Fuyubi; Hirano, Katsuya; Ishihara, Mai; lewallen, ann-elise; Lightfoot, Sheryl; Mayunkiki; Medak-Saltzman, Danika; Williams-Davidson, Terri-Lynn; Yahata, Tomoe
ABSTRACT: This roundtable presents the proceedings of the "Hokkaidō 150: Settler Colonialism and Indigeneity in Modern Japan and Beyond" workshop held at the University of British Columbia in March 2019. The sesquicentennial of Japanese settler colonization of the northern island of Hokkaidō or Ainu Mosir received only scant attention either in Japan or around the world. The goal of this roundtable is to reinsert settler colonialism into modern Japanese history while introducing the case of the Ainu into global conversations of Indigeneity. Katsuya Hirano draws attention to how the Meiji state manipulated ideas of ownership to enable exploitation of Ainu lands. ann-elise lewallen recenters Ainu women's resistance to the sexual colonization of Hokkaidō. Mai Ishihara interrogates her own positionality and asks why many people with Ainu heritage remain silent. Sheryl Lightfoot reviews how the case of the Ainu in Hokkaidō complicates prevailing paradigms of settler colonial studies. Musicians Mayunkiki, Tomoe Yahata, and Terri-Lynn Williams-Davidson discuss issues of Indigenous identity and their practice. Finally, Danika Medak-Saltzman concludes the roundtable by re-situating Ainu at the intersection of settler colonial and Native studies, challenging Japan scholars to more meaningfully engage and prioritize Indigenous studies.